Transannular Selenocyclofunctionalization of 1,5-cyclooctadiene: The Antioxidant Properties of 9-selenabicyclo[3.3.1]nonane Derivatives and the Discovery of Increasing Both GPx and GR Activities - Maxim V. Musalov; Irina S. Kapustina; Ekaterina V. Spiridonova; Natalya V. Ozolina; Svetlana V. Amosova; Tatyana N. Borodina; Vladimir A. Potapov (Inorganics, 2023)
Oxidative stress is the cause of various pathologies and disorders of cellular functions. Substances that reduce the pathological effect of oxidative stress on homeostasis include organoselenium compounds of natural and synthetic origin. Depending on the structure, organoselenium compounds can exhibit different biological activities, for example, reducing oxidative stress, participating in the regulation of signaling systems, influencing the synthesis of cytokines, etc. This makes them promising products for the development of new means of metabolic correction and drugs with enzyme-like activity. This study is aimed at developing an effective method for the synthesis of functional organoselenium compounds and studying their antioxidant effect in vivo under stress conditions. A one-pot catalyst-free method of transannular addition-functionalization of cis,cis-1,5-cyclooctadiene with selenium dihalides in the presence of nucleophiles was developed. For the first time, the antioxidant activity of functionalized 9-selenabicyclo[3.3.1]nonanes was studied in vivo. Quantitative characteristics of the effect on the level of lipid peroxidation and the activity of glutathione peroxidase and glutathione reductase under stress conditions were obtained. The effect of substituents in the selenium-containing scaffold on the biological activity of the compounds was studied. The water-soluble 9-selenabicyclo[3.3.1]nonane derivatives, containing hydroxyl and 2-hydroxyethoxy groups, which increased the activity of both glutathione peroxidase and glutathione reductase, were discovered.